(untitled) - Rich, Elaine (New Delhi, 2009)
The book develops the theory and practice of heuristic search, providing detailed algorithms for standard search method. It also explores a variety of methods for encoding knowledge in computer systems. There are also chapters on both symbolic and numeric techniques for reasoning under uncertainty
Keywords: Artificial intelligence,Trí tuệ nhân tạo